“The importance of interpretation and basic features of phraseological units” (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article revolves around the central concept of interpretation and its key variations. It primarily delves into the study of phraseology as a linguistic branch. Phraseological units exhibit several distinctive features that set them apart from other types of expressions. These features contribute to the fixed nature and specific meanings of phraseological units. Similar to individual words, phraseologisms are fixed units in language and exist within every phrase. They are considered as lexical units, akin to words, and are not just part of speech events but are integral to language events. The article also delves into the examination of phraseology, discussing the stages of its formation and its primary characteristics.